Statistics of indicators of school libraries in the Republic of Moldova in 2012 year (Confluenţe Bibliologice, 2026)
In this article are analyzed cumulative statistical reports on activity of school libraries in 2012 year. There are presented the regions: the North region - Departmental Libraianship Centre within the Scientific Library of Alecu Russo State University in Balti;  Central and South Regions - Libraianship Centre wihtin „Ion Creanga" State Pedagogical University of Chisinau. The indicators analysed are: General data, collections, purchases, users and the library's users, electronic services, the librarian’s staﬀ. This  year was realized by the University Library of Balti total integration of statistical indicators into a single summary table.
Keywords: Departmental Librarianship Center; statistical reports; statistical indicators